2020
DOI: 10.18502/sbrh.v4i2.4680
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Distribution of Divorce Causes in Yazd City

Abstract: Background: Divorce, as a consequence of family disruption, is a common phenomenon within all communities. Considering the increased frequency of divorce cases in Yazd city during recent years, this study was conducted to investigate the distribution of divorce causes and design an efficient program to deal with it. Methods: This descriptive cross-sectional analytic study was conducted on the data collected from 118 male and female individuals referred to Yazd courts with divorce requests during  12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on the inclusion criteria, 16 studies were selected and further reviewed, the results of which are shown in [ Table 1 ]. Among the reviewed articles, five were cross-sectional articles[ 16 , 19 , 20 21 22 ] eight were descriptive articles[ 12 13 14 , 17 , 23 , 27 28 29 ], 2 were qualitative studies[ 26 , 30 ], and one was a quantitative and survey study[ 24 ]. The instruments used in these studies included researcher-made questionnaires, in-depth interviews, standard questionnaires, or records in the files of divorced individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the inclusion criteria, 16 studies were selected and further reviewed, the results of which are shown in [ Table 1 ]. Among the reviewed articles, five were cross-sectional articles[ 16 , 19 , 20 21 22 ] eight were descriptive articles[ 12 13 14 , 17 , 23 , 27 28 29 ], 2 were qualitative studies[ 26 , 30 ], and one was a quantitative and survey study[ 24 ]. The instruments used in these studies included researcher-made questionnaires, in-depth interviews, standard questionnaires, or records in the files of divorced individuals.…”
Section: Resultsmentioning
confidence: 99%